Displays of the Garganey Anas querquedula: Evidence of multiple functions - Pearce, Alison N (Wildfowl, 2000)
Male dabbling ducks use displays in two main contexts: courtship of females and hostile encounters with other males. Although the displays associated with each of these situations are fairly well documented, the use of particular displays in both situations has only been reported in a few species. The social behaviour of the Garganey (Anas querquedula) was investigated to provide a detailed account of the frequency with which displays are performed, study the orientation component of the displays, and examine the possibility that males of this species may use displays in multiple contexts. Displays that have previously been described as functioning only in courtship are also used by Garganey males in hostile situations. In particular, males direct the burp and laying-the-head-back toward rival males when competition for females is intense. Previous researchers have postulated that the presence of long-term pair bonds may contribute to the development of rivalries and, potentially, multiple use displays. Use of multiple function displays by Garganey males suggests that other factors may contribute to this behavioural phenomenon. Careful analyses of behavioural displays can also be useful in examining evolutionary hypotheses, although information on the displays of many other dabbling ducks is still needed to fully evaluate conflicting phylogenies.